Peningkatan Kemampuan Belajar pada Mata Kuliah Belajar dan Pembelajaran Melalui Metode Kooperatif - Aliahardi Winata; Deviana Mayasari; Zedi Muttaqin (Universitas Muhammadiyah Mataram, 2023)
Learning and learning are compulsory courses taught to students with the aim of forming and changing the mindset of students. The method used in learning needs to be determined, this is the running of the learning process. In this study, the method used was the cooperative method. The success of the work is greatly influenced by the involvement of each member of the group. Cooperative learning in this study was carried out Plan, Do, See, namely lesson study. The research was conducted at the Pancasila and Citizenship Education Study Program in the 3rd semester of the University of Muhammadiyah Mataram. The research subjects were 16 students of the Pancasila and Citizenship Education Study Program. This research was conducted from 6 to 30 October 2017. This type of research is quantitative research with an action approach through lesson study activities. The results of the research